Arts in Earnest : North Carolina Folklife - Zug, Charles G., III; Patterson, Daniel W. (Daniel Watkins), 1928- (Book collections on Project MUSE., 1990)
Arts in Earnest explores the unique folklife of North Carolina from ruddy ducks to pranks in the mill. Traversing from Murphy to Manteo, these fifteen essays demonstrate the importance of North Carolina's continually changing folklife. From decoy carving along the coast, to the music of tobacco chants and the blues of the Piedmont, to the Jack tales of the mountains, Arts in Earnest reflects the story of a people negotiating their rapidly changing social and economic environment. Personal interviews are an important element in the book. Laura Lee, an elderly black woman from Chatham County, des.